STUDI PENGENDALIAN PEMANAS PADA REAKTOR HIDROGENASI MINYAK NABATI MENJADI GREENDIESEL DENGAN JAKET PEMANAS - Setyawan, Martomo (Universitas Ahmad Dahlan, 2014)
Greendiesel is the second generation of the biodiesel fuel. The advantages of greendiesel compareÂ with first generation of biodiesel are higher cetane number, no waste on the production and low CO2 emission. Greendiesel was made from vegetable oil with hydrogenation process at the high temperature and high pressure, this process has high risk to explode. This research was to study about heat transfer mechanism from electric heat source to the reactor with avoid explode, by to avoid hydrogen contact with high temperature above 500 OC.Heat transfer mechanism on the hydrogenation reactor was designed from electric heat source transferred to the oil heater and then to the reactor. At this research was studied effluence of the electric voltageÂ to the temperature of the heating oil and the water inside at the reactor.The Result of this research was show increasing voltage cause increasing speed of heating. At the all voltage increasing heating speed occur until 40 minutes as linier and after 40 minutes the heating speed decrease as logarithmic. By indirect heating by electric source contact between hydrogen and high temperature surface can be avoided.